Efeitos de priming translinguístico em brasileiros aprendizes de inglês em níveis intermediário e avançado - Silva, Artur Paulino da (2019)
The main goal of this research lies on investigating the cross-language influence at the semantic level in English-speaking Brazilians as L2. Considering the Experimental Psycholinguistics context, questions about cross-language influence on bilinguals have gained prominence in several foreign languages such as English and French (PHILIPS et al., 2004), Basque and Spanish (PEREA et al., 2008), as well as in Portuguese and Spanish SOUZA et al., 2014). Likewise, we assume that this type of influence may occur at the semantic level. To do so, we propose an experiment with methodology of masked priming using a lexical decision task in order to collect data As independent variables, we have the level of proficiency, (intermediate and advanced), the semantic relationship between the words of L1 and L2 (now related, now unrelated), as well as the direction of cross-language influence (either L1-L2, or L2 -L1). The prime words were shown in lowercase letters and the target words in uppercase. The dependent variable was the reaction time in milliseconds. As well as in Perea et al. (2008) paper, forty (40) pairs of words related and not semantically related as stimulus, in English and Portuguese language, respectively, were chosen, for example milk / COW, letter / PRAIA. 39 participants were invited for the first experiment and 31 for the second experiment. All of them adults, Brazilians and learners of English as a foreign language. They were divided according to proficiency level: 20 intermediate, and 19 advanced participants for the first experiment. For the second experiment 16 intermediate and 15 advanced participants were invited. For this distinction, we used the Vocabulary Level Test (VLT) (NATION, 1990 apud OLIVEIRA, 2015). The results of the first experiment demonstrated a proficiency effect in which the students in advanced level processed faster than the intermediates in all cases; it was also found a language effect in which the L2-L1 stimuli were faster than L1-L2; regarding the semantic priming it was found a significant effect but in an opposite direction in which the unrelated words were processed faster than the related ones. Thus, in the second experiment it was found a similar effect of language proficiency and semantic relation similar to the findings of Perea et al. (2008). In addition, our results support the Revised Hierarchical Model, which states that lexical and conceptual links are active in bilingual memory, but it strengths change as L2 proficiency increases.